2021
DOI: 10.3390/biology10080805
|View full text |Cite
|
Sign up to set email alerts
|

Natural Pest Regulation and Its Compatibility with Other Crop Protection Practices in Smallholder Bean Farming Systems

Abstract: Common bean (Phaseolus vulgaris) production and storage are limited by numerous constraints. Insect pests are often the most destructive. However, resource-constrained smallholders in sub-Saharan Africa (SSA) often do little to manage pests. Where farmers do use a control strategy, it typically relies on chemical pesticides, which have adverse effects on the wildlife, crop pollinators, natural enemies, mammals, and the development of resistance by pests. Nature-based solutions —in particular, using biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 167 publications
0
10
0
Order By: Relevance
“…Spring migration from the spindle trees may have been low during the test year due to poor autumn or winter conditions (Cammel et al, 1989). Heavy showers, strong winds, and relatively low spring temperatures (Nikolova, 2019) along with the presence of natural enemies would have contributed to the slow population growth (Dixon, 1977; Ndakidemi et al, 2021; Way, 1966). Nevertheless, the large difference between ILB938/2 and Columbo was maintained, supporting our earlier suggestion that ILB938/2 has an antagonistic effect on the performance of the black bean aphid (Morvan, 1987; Shannag & Ababneh, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Spring migration from the spindle trees may have been low during the test year due to poor autumn or winter conditions (Cammel et al, 1989). Heavy showers, strong winds, and relatively low spring temperatures (Nikolova, 2019) along with the presence of natural enemies would have contributed to the slow population growth (Dixon, 1977; Ndakidemi et al, 2021; Way, 1966). Nevertheless, the large difference between ILB938/2 and Columbo was maintained, supporting our earlier suggestion that ILB938/2 has an antagonistic effect on the performance of the black bean aphid (Morvan, 1987; Shannag & Ababneh, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The first treatment factor was for experimental plots with field margin vegetation planted with four plant species (Appendix S1). The field margin plant species were selected based on their relative abundance in the ecosystem and previous studies, which indicated their role in supporting beneficial insects (Ditner et al, 2013; Ndakidemi et al, 2021). The plant species were Chenopodium album (Amaranthaceae), Bidens pilosa (Asteraceae), Galinsoga parviflora (Asteraceae) and Tagetes minuta (Asteraceae).…”
Section: Methodsmentioning
confidence: 99%
“…However, faba bean production faces numerous challenges, including various insect pests that can significantly impact yield and quality. Among these pests, the black bean aphid (Aphis fabae S.) (Hemiptera: Aphididae) stands out as a major threat, causing substantial economic losses in many faba-bean-growing regions [1,2].…”
Section: Introductionmentioning
confidence: 99%